2016
DOI: 10.1104/pp.16.00035
|View full text |Cite
|
Sign up to set email alerts
|

The Raf-like kinase ILK1 and the high affinity K+ transporter HAK5 are required for Innate Immunity and Abiotic Stress Response

Abstract: Plant perception of pathogen-associated molecular patterns (PAMPs) and other environmental stresses trigger transient ion fluxes at the plasma membrane. Apart from the role of Ca 2+ uptake in signaling, the regulation and significance of PAMPinduced ion fluxes in immunity remain unknown. We characterized the functions of INTEGRIN-LINKED KINASE1 (ILK1) that encodes a Raf-like MAP2K kinase with functions insufficiently understood in plants. Analysis of ILK1 mutants impaired in the expression or kinase activity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 71 publications
2
95
0
1
Order By: Relevance
“…Interestingly, flg22 treatment triggers a considerably higher peak value of Cl − efflux than of H + influx, suggesting the involvement of anion channels in establishing PM depolarization (66). Integrin-linked kinase 1 (ILK1), which interacts with the high-affinity K + transporter HAK5, positively regulates flg22-induced PM depolarization, implicating the involvement of K + efflux in PM depolarization (16). Ca 2+ signaling likely functions upstream of PM depolarization and extracellular alkalinization, as lanthanum, a PM Ca 2+ channel blocker, inhibits flg22-induced PM depolarization (66).…”
Section: Cellular and Physiological Responses Triggered By Patternsmentioning
confidence: 99%
“…Interestingly, flg22 treatment triggers a considerably higher peak value of Cl − efflux than of H + influx, suggesting the involvement of anion channels in establishing PM depolarization (66). Integrin-linked kinase 1 (ILK1), which interacts with the high-affinity K + transporter HAK5, positively regulates flg22-induced PM depolarization, implicating the involvement of K + efflux in PM depolarization (16). Ca 2+ signaling likely functions upstream of PM depolarization and extracellular alkalinization, as lanthanum, a PM Ca 2+ channel blocker, inhibits flg22-induced PM depolarization (66).…”
Section: Cellular and Physiological Responses Triggered By Patternsmentioning
confidence: 99%
“…Animal ILKs contain abundant substitutions in conserved residues of the KD and, although their kinase activity may be possible, extensive analyses substantiate the view that they are true pseudokinases (Wickström et al, 2010). By comparison, plant ILKs contain fewer substitutions and some, at least, can catalyze a phosphotransfer reaction, in both autophosphorylation and substrate phosphorylation assays (Chinchilla et al, 2008; Brauer et al, 2016). …”
Section: Structural Features Of Ilkssmentioning
confidence: 99%
“…Notably, despite lacking transmembrane regions, several ILKs were found associated with the PM or intracellular membranous organelles. ILK1 co-localized with the PM and ER markers (Brauer et al, 2016), and ILK4 and ILK6 were identified in the PM, Golgi and tonoplast (Benschop et al, 2007; Whiteman et al, 2008; Elmore et al, 2012; Heard et al, 2015). ILK4 and ILK5 may be nuclear-localized as predicted by the bipartite or monopartite nuclear localization signals within their C-termini ( Figure 1 ); an ILK5-GFP fusion was detected both in the cytosol and nucleus (Koroleva et al, 2005; Ito et al, 2011).…”
Section: Regulation Of Ilksmentioning
confidence: 99%
See 2 more Smart Citations